Measure what matters: A survey-based examination of health equity tracking and measurement practices across healthcare systems in the United States. - Hallie Roth; Emilia De Marchis; Karyl Kopaskie; Alexandra Restall; Caroline Fichtenberg; Shaifali Ray; Kristen M J Azar (PLoS ONE)
The objectives of this study were to understand how healthcare systems are incorporating equity into performance measurement and to uncover trends that inform healthcare systems' efforts to advance equity. A national cross-sectional survey was designed and administered during Spring 2022 to evaluate organizational efforts to track and measure health equity. The survey examined clinical and non-clinical health equity metrics/indicators tracked at the executive-level. We identified variation in how health equity is measured. Of the 27 respondents, seven (25.9%) were in the planning phase, nine (33.3%) were in early implementation, seven (25.9%) had practices implemented for one to two years, and four (14.8%) had practices implemented for three or more years. Most systems were tracking clinical metrics and evaluating metrics across subpopulations. Metrics related to chronic disease management and preventive care were mentioned most frequently (23.6% and 16.0%, respectively). Race/ethnicity was the most utilized demographic filter to evaluate equity. Systems at later stages of implementation were tracking fewer metrics, yet many systems were still in early stages of implementation. Health systems need specific and pragmatic guidance to develop and implement equity measures tracked at the executive level. Insights from current health system initiatives can help inform guidelines from national quality organizations for disparity reduction in clinical outcomes.